Effects of Sewage Sludge on Tree Growth, Soil Properties and Groundwater Quality - Abdu, Arifin (2005)

(untitled)
Effect of sewage sludge on the growth of plants is well documented for many agricultural and horticultural crops but limited research has been conducted on forest trees. The organic matter in sewage sludge can improve the soil physical and chemical properties but it also contains varying amounts of heavy metals that may cause toxicity and potentially can contaminate the groundwater. Thesis reports two studies on the effects of sewage sludge on tree growth, foliar nutrients, soil properties and groundwater quality. The first study was conducted in the greenhouse with using two timber species viz Dyera costulata and Cinnamomum iners. Factorial experiments of 10 x 2 x 4 were conducted to study the effect of sewage sludge on the growth performance and foliar nutrient concentrations at the 10 levels of treatment. After six months of treatment, the results showed that T7 (70% of sludge by volume) and T6 (60% of sludge by volume) gave the highest height and growth diameter for D. costulata and C. iners, respectively. The use of sewage sludge at the rate of more than 70% for D. costulata and 60% for C. iners did not gave the significant different in terms of height, diameter and foliar nutrient concentrations. The study also indicates that the critical nutrient levels for D. costulata and C. iners were correspond to treatments 6 and 7, respectively. The second study was a field experiment with comprising of five tree species viz S. leprosula, D. costulata, A. mangium, C. iners and H. odorata using t-test comparing two main treatments; plots treated with sewage sludge at the rate of 4050 m3/ha and a control (untreated). The results showed that all the species treated with sewage sludge were significantly higher in terms of height and growth diameter compared than the corresponding species in the control plot. The concentrations of foliar nutrients in the five species were significantly higher (P10.05) in the treated than the corresponding trees in the control plots. This implies that sewage sludge significantly affected the concentration of foliar nutrients uptake. The fertility of the soil for both macronutrient (N, PI K, Ca, Mg and Na) and micronutrients (Mn, Zn, Fe and Cu) in the treated plot were also higher than the control plots. However, the concentration of micronutrients and other heavy metals in the foliar and soil did not exceed the maximum permitted concentrations (MPC) of the European Community Standard (ECS). Water quality monitoring showed that the groundwater within the experimental area was contaminated with organic contaminants and nutrient compounds. The concentrations of arsenic, manganese, ammoniacal-nitrogen, phenol, BODS and COD exceeded the limits recommended by the national guidelines for drinking water quality. The presence of E. coli in the groundwater samples indicated that the samples had been contaminated with this organism. Generally, this study indicates that sewage sludge significantly affects tree growth, foliar nutrient concentrations, soil properties and groundwater quality. Disposal of sewage sludge therefore has to be thoroughly monitored to avoid soil and groundwater contaminations.